2021
DOI: 10.1108/jiabr-06-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

State ownership and bank performance: conventional vs Islamic banks

Abstract: Purpose This paper aims to examine the effect of state ownership on bank performance for all banks in the Gulf Cooperation Council (GCC) countries during the period 2003 – 2018, for two distinct banking systems: the conventional and the Islamic banking systems. Design/methodology/approach To achieve the goal of the study, this paper uses a mean t-test to examine the mean difference of the related variables for both banking systems, and a regression test (using the GMM method) to explore the effect of state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Bank size is measured by calculating the natural logarithm of total assets. Most previous studies confirm that large banks are more profitable than smaller-sized banks (Alharthi, 2017b;Alshammari, 2021;Başar et al, 2021;Boussaada & Hakimi, 2021;Rehman, Aslam, & Iqbal, 2022;Saadaoui & Mokdadi, 2022). In contrast, a few studies argue that a smaller total assets value leads to larger earnings (Al-Matari, 2021).…”
Section: Bank Size and Financial Performancementioning
confidence: 98%
See 3 more Smart Citations
“…Bank size is measured by calculating the natural logarithm of total assets. Most previous studies confirm that large banks are more profitable than smaller-sized banks (Alharthi, 2017b;Alshammari, 2021;Başar et al, 2021;Boussaada & Hakimi, 2021;Rehman, Aslam, & Iqbal, 2022;Saadaoui & Mokdadi, 2022). In contrast, a few studies argue that a smaller total assets value leads to larger earnings (Al-Matari, 2021).…”
Section: Bank Size and Financial Performancementioning
confidence: 98%
“…Examples are the studies by Alshammari (2021) and Saif-Alyousfi and Saha (2021) on GCC countries, and the study by Sahyouni and Wang (2019) on countries in the Middle East and North Africa (MENA) region. Conversely, Alharthi (2017a) and Manlagñit (2011) found that loan intensity decreases profits significantly.…”
Section: Loan Intensity and Financial Performancementioning
confidence: 99%
See 2 more Smart Citations
“…First, macroeconomic factors by considering financing, operational and liquidity risks. Second, comparisons between Islamic banks and conventional banks are carried out due to differences in the operational systems of each bank, and third consider adding a standard deviation indicator of profitability for three years as income uncertainty due to operating expenses in testing the influence of operational risk (Hidayat et al, 2021), (Alshammari, 2021), (El-Chaarani et al, 2022), (Lebdaoui & Chetioui, 2020) dan (Akkas & Asutay, 2022). These differences will be evaluated based on two main characteristics, namely firmspecific risk and macroeconomic factors faced by the two groups of banks and their impact on performance in terms of profitability, so as to increase the performance of Islamic banks in particular those still affected by the COVID-19 crisis.…”
Section: Roa Of Islamic Banksmentioning
confidence: 99%